O uso de referentes pessoal e de lugar e o uso de formulações em interrogatórios na corte - Andrade, Daniela Negraes Pinheiro (Universidade do Vale do Rio dos Sinos, 2010)
This study, supported by Ethnomethodological (GARFINKEL, 1967) Conversation Analysis theoretical-analytical approach (SACKS; SCHEGLOFF; JEFFERSON, 1974) combined with ethnographic methods (O’REILLY, 2009), focuses on the description of person reference (STIVERS, 2007; STIVERS et al., 2007), place reference (SACKS, 1992; SCHEGLOFF, 1972; PSATHAS, 1991), and formulation usage (SACKS ; GARFINKEL, 1970; HERITAGE, 1995; WALKER, 1995; HERITAGE; WATSON, 1979; DREW, 2003; GAFARANGA; BRITEN, 2004, HUTCHBY, 2005; ANTAKI et al., 2005) b y Law professionals in face-to-face interactions with defendants, victims, and wit nesses in court interrogations. The law professionals who participated in this study are two judges (one male one female), three prosecutors, and nine defense lawyers. The data comprise 59 audio-recorded interrogations which took place in a criminal court located in a metropolitan area in Southern Brazil. Data collection was carried out between August and November of 2008. Of the analyzed interrogations, 31 were chaired by the male judge and 28 were chaired by the female judge. Of the interrogatories presided by the male judge, 27 took place in examining hearings and four in Jury Trials. All of the interrogatories chaired by the female judge took place in examining hearings. The discussion has two analytical focuses. The first one deals with the interactional actions Law professionals achieved through the use of person and place references, which are: a) to cross-examine the versions provided by different deponents related to the same crime; b) to feedback the interrogatory through questions which demand third person identification; c) to deal with coparticipants' intersubjectivity (HERITAGE, 1984) when the shared recognition concerning “who is who” and “what place we are talking about” seems jeopardized. The second analytical focus concentrates on the interactional actions implemented by professional participants via formulation, which are: a) to check understanding as to attend the institutional agenda requirement of recording the pieces of information provided by the deponents; b) to manage the professional agenda through the interactional move of closing a topic and opening other as to cover the relevant subjects for the current interrogatory; c) to confront the deponents’ versions; d) to invite the deponent to vocalize some piece of information which appears relevant to the process in such a way that what has been said becomes recordable according to the procedures required by the institution; e) to fill in the referential term alluded to but not made explicit by the deponent. The interactional analysis also reveals that the distribution format of formulations during the interrogatory takes two different formats: a) a sequence of formulations that culminates in an “ulterior” formulation and b) a formulation displayed after an “alleged” accountability provided by the professional participant. The study makes clear that both the person and place reference usage and the formulation practice play important roles in juridical-type interactions and shows them, on some occasions, to be essential for the interrogatory development and, consequently, for the juridical process as a whole
Keywords: Análise da conversa; Formulação; Referentes pessoal e de lugar; Interrogatórios na corte; Conversation analysis; Formulation; Person and place reference; Court interrogation; ACCNPQ::Lingüística, Letras e Artes::Lingüística